The Effect of Child-Friendly Joyful Learning on Data Processing Materials on the Mathematical Analysis Skills of Grade VI Students of Madrasah Ibtidaiyah - Muhammad Fiqri Alwi; Rora Rizky Wandini (MASI Mandiri Edukasi, 2026)
Many elementary students struggle to develop mathematical analysis skills, particularly in data processing, due to the dominance of teacher-centered learning approaches that limit student engagement. This study aims to examine the effect of a child-friendly Joyful Learning model on the mathematical analysis skills of sixth-grade students in an elementary madrasah. A quantitative, quasi-experimental design was employed in this study. The participants were 70 sixth-grade students at MIN 4 Medan City, divided into an experimental and a control class. The experimental class was taught using the child-friendly Joyful Learning model, while the control class received conventional instruction. Data were collected through classroom observation and a mathematical analysis ability test in the form of essay questions. The data were analyzed using N-gain analysis and an Independent Samples T-Test. The results showed that students in the experimental class achieved a high N-gain score of 0.84, whereas those in the control class achieved a moderate N-gain score of 0.35. Hypothesis testing revealed that the calculated t value exceeded the critical value at the p < 0.001 significance level, indicating a statistically significant difference between the two groups. These findings demonstrate that the child-friendly Joyful Learning model is effective in enhancing students’ mathematical analysis skills when processing data. Therefore, this learning model can be considered an effective alternative instructional approach for improving mathematics learning outcomes at the elementary school level.